Overcoming Digital Inequalities—Identification and Characterisation of Digitally Resilient Schools in Different Countries Using ICILS 2023 Data - Jan Niemann; Birgit Eickelmann; Kerstin Drossel (Education Sciences)
(1) Background: As digitalisation transforms society, digital competences are increasingly essential. Yet students’ digital competences often vary significantly, largely influenced by socio-economic background. Some schools—termed “resilient schools”—effectively counter these disadvantages and foster high digital competence. This study investigates the prevalence of such schools and examines how they differ from others. (2) Methods: Drawing on representative ICILS 2023 data, quantitative secondary analyses—including descriptive statistics, t-tests, and multiple regression—were conducted. Following the identification of resilient schools, in-depth analyses focus on those countries with substantial proportions of resilient schools above 10 percent (Austria, Italy, and Portugal), as these countries seem to have effective strategies to foster school resilience. (3) Results: The findings highlight considerable cross-national variation, indicating that school resilience is context-dependent. Resilient schools consistently emphasise student learning-related factors—such as ICT-related attitudes and educational aspirations—while the influence of home environments is less pronounced than in other schools. (4) Conclusions: Strengthening student learning-related factors appears to be crucial for building digital resilience. These insights can inform policy and practice aimed at fostering educational equity and closing the digital divide, particularly in socio-economically disadvantaged contexts.